The feasibility and safety of repeat cryosurgical ablation of localized prostate cancer. Issue 1 (December 2015) - Mustafa, Mahmoud; Delacroix, Scott; Ward, John; Pisters, Louis
Abstract Background The aim of the study was to assess the morbidity and efficacy of repeat cryoablation (CA) in the treatment of localized prostate cancer. Methods Twenty-seven patients with median age of 71 years (range 48–80) who underwent repeat CA between April 2003 and April 2011 at a single institution were included. The median initial prostate-specific antigens (PSA) and Gleason values were 6.2 ng/ml (range 4–23.6) and 7 (range 6–9), respectively. Twenty-four patients underwent two CA treatments, and three patients underwent three CA treatments. Pre- and perioperative parameters and oncological and functional outcomes were evaluated. Results No intraoperative complications occurred. After the first CA, PSA was undetectable in 10 patients, and the median nadir PSA value was 0.65 ng/ml (range 0.1–4.9). After the second CA, 4 patients had undetectable PSA, and the median nadir PSA value was 1.25 ng/ml (range 0.2–7.9). For patients who underwent a third CA treatment, no patients had undetectable PSA, and the subsequent median nadir PSA value was 1.6 ng/ml (range 0.4–4.5). Two patients had incontinence (1 pad per day) following repeat CA. One patient had urinary retention after the third CA treatment, and one had urethral stricture. The mean hospitalization and follow-up periods were 1 day (range 0–2) and 51.5 months (range 11–96), respectively. Conclusions Repeat CA successfully reduced PSA levels, and complications were modest. We conclude that repeat CA is a feasible, safe, and effective treatment option for localized prostate cancer.